Analysis of profitability, leverage and sales growth on stock prices with liquidity as intervening variables in garment and textile companies listed on IDX 2015-2020 - Kiki Astrida; Zulkifli Zulkifli; Syamsul Bahri (Universitas Negeri Padang, 2022)
This study is to see the effect of profitability, leverage and sales growth on stock prices and later mediation by liquidity in textile and garment companies listed on the Indonesia Stock Exchange in 2015-2020. This study uses a quantitative and explanatory approach with a population of all manufacturing companies in the various textile and garment sub-sector industries as many as 21 companies, so that a sample with the number of data observations (N) is 96 observations for each variable (16 companies x 6 years). research period). The type of secondary data with data sources is the company's website and also www.idx.go.id. The data analysis technique is Structural Equation Modeling using PLS software. The research findings show: 1) profitability has a significant effect on liquidity, 2) leverage has a significant effect on liquidity, 3) sales growth has no significant effect on liquidity, 4) profitability has no significant effect on stock prices, 5) leverage has a significant effect on stock prices, 6 ) sales growth has no significant effect on stock prices, 7) liquidity has no significant effect on stock prices, 8) profitability has no significant effect on stock prices through liquidity, 9) leverage has no significant effect on stock prices through liquidity, 10) sales growth has no effect significant effect on stock prices through liquidity.